Self-management: understanding, communicating, and assessing behavioral competency - Mr. Gian Paolo Roma ([Place of publication not identified] : [Publishers name not idntified], 2019)
Each year millions of academically capable students drop out of high school and college for non-financial reasons. It is a troubling problem that highlights the need for students to be more resilient, prepared, and effective at reaching their goals. How can students position themselves to succeed in this increasingly demanding, changing, and competitive world? One way is to understand and practice the basic behaviors necessary to achieve goals. The third edition of "Self-Management: Understanding, Communicating, and Assessing Behavioral Competency" offers an innovative approach to student success, which focuses on improving student behavior. Behaviors communicate a great deal. Because certain behaviors lead to better academic performance than others, it is essential that students learn about the relationship between behavior and academic performance.The main reason that individuals should study things like one$1 (Bs own desires, values, thinking, choices, and behavior is to get one$1 (Bs system of thinking in order so that one can anticipate and avoid many of the struggles that one might walk into head first if one walked through life blindly. The main purpose of this book is to help students achieve their goals by clarifying the behaviors that they alone are responsible for, showing why they are important, and how they lead to success. This book introduces a comprehensive self-management model to help students understand and assess their own behavioral performance. The book provides a practical framework, how to exercises, a new behavioral observation measurement system, behavioral profile, self-tests, and a behavioral change methodology for individuals, families, and schools seeking to establish, assess, and improve behavioral performance. Professor Roma can be reached at romag@sunybroome.edu. He gets many emails and will try to respond to yours as quickly as he can. He usually doesn$1 (Bt answer calls from unrecognized phone numbers, so please leave a message if he doesn$1 (Bt answer, and he will call you back as soon as he is able. Mr. Gian Paolo RomaProfessor and Chair of the Business Programs DepartmentSUNY Broome Community CollegePO Box 1017 Binghamton, NY 13902Office: (607) 778-5133s
Keywords: Management; Understanding; Communicating